Analytical Review On Resources, Funding, And Decisions (2009-2017) The Role Of The Adaptation Fund In The International Climate Change Adaptation Finance - Serdouk, Fateh (University of eloued - جامعة الوادي, 2018)
The aim of this paper is to provide background information to facilitate the analytical review of the Adaptation Fund resources and funding, in line with the objective scope under adaptation to climate change as a financial mechanism promoting the international climate finance within the united nations framework convention on climate change (UNFCC).as well as giving a critical review of the adaptation fund decisions. This paper also examines the AF’s governance framework and the AF’s policies and guidelines placed to ensure the integrity of its Board and thereby decisions. The sources of information for this paper are through the trustee periodical reports of the adaptation fund, as well as the adaptation fund board decisions. Furthermore, this paper recapitulates and analyzes the outcomes financial reports of the World Bank as fund Trustee. Furthermore, the focus on the analytical review in this paper is for the period from 2008 When the legal framework of the Fund was established by its key documents adopted at the 2008 climate summit in Poznań, Poland, considering 2009 as an inception year, to the latest Adaptation Fund Trust Fund Financial Report, as of December 31, 2017.
مقال
Keywords: Climate change; Adaptation Fund; Resources; Funding decisions. UNFCCC.